2011
DOI: 10.1111/j.1365-2427.2011.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary changes in dissolved organic carbon (DOC) in human‐dominated rivers: is there a role for DOC management?

Abstract: 1. Dissolved organic carbon (DOC) plays a central role in the dynamics of stream and river ecosystems, affecting processes such as metabolism, the balance between autotrophy and heterotrophy, acidity, nutrient uptake and bioavailability of toxic compounds. However, despite its importance to stream processes, restoration and management activities rarely incorporate DOC as a major management criterion. 2. Lotic DOC pools reflect terrestrial organic carbon accumulation, transfer to the river channel and aquatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
202
0
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(221 citation statements)
references
References 170 publications
(257 reference statements)
7
202
0
12
Order By: Relevance
“…All these fundamental aspects can potentially be impacted by human activities (Stanley et al 2012). In this study, we showed that human activities in the Walloon region have affected both terrestrial and aquatic sources of fluvial OM, leading to a shift in composition toward a more microbial/algal and less plant/soil-derived character in streams and rivers.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…All these fundamental aspects can potentially be impacted by human activities (Stanley et al 2012). In this study, we showed that human activities in the Walloon region have affected both terrestrial and aquatic sources of fluvial OM, leading to a shift in composition toward a more microbial/algal and less plant/soil-derived character in streams and rivers.…”
Section: Resultsmentioning
confidence: 92%
“…A similar pattern was observed at the scale of the Meuse basin whereby F Max of terrestrial components were slightly higher during S2 (summer period, low specific discharge) relative to S1 (winter period, high specific discharge). This likely reflects modification and/or reorganization of hydrological flow paths that connect terrestrial soils to aquatic ecosystems by agricultural practices and urbanization engineering (Kaushal and Belt 2012;Stanley et al 2012).…”
Section: Seasonal Fluctuation In Fluvial Om and The Impact Of Human Amentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter may also be directly deposited into streams and can contribute to depleted dissolved oxygen (DO) concentrations, thus threatening ecosystem health (Imberger et al 2014). Investigating and controlling concentrations of both nutrients and OM should be considered when developing eutrophication mitigation strategies (e.g., Smith et al 1999;Dodds 2007;Stanley et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given the role of allochthonous DOC in supporting and structuring aquatic ecosystems, there are a wealth of opportunities to incorporate DOC to support process-based river rehabilitation and management (Stanley et al 2012). To build on this interest in allochthonous DOC in management, Baldwin et al (2016) present a review paper on the use of environmental flows to restore allochthonous DOC to lowland river systems.…”
Section: Management Of Allochthonous Docmentioning
confidence: 99%